IMPLEMENTATION OF GROUNDWATER USAGE REDUCTION POLICY IN SOUTH JAKARTA - Apriansyah, Joli; Izzatusholekha, Izzatusholekha; Satispi, Evi (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
The accelerated urbanization of Jakarta is precipitating substantial transformations in the city's physical landscape, driven by urban planning initiatives, particularly in the realm of water resource management, with a pronounced reliance on groundwater. This surge in groundwater extraction, notably prevalent in South Jakarta, has led to increased land subsidence, necessitating the enforcement of Governor Regulation Number 162 of 2012. This regulatory framework delineates directives for water resource management, tailored to address the extensive use of groundwater in South Jakarta. This research aims to comprehensively analyze the implementation of policies designed to curtail groundwater usage in South Jakarta. Employing George Edwards III's Policy Implementation framework, four crucial indicators—communication, resources, disposition, and bureaucratic structure—are systematically investigated. Utilizing a descriptive, qualitative approach with data gathered through interviews, observations, and document analysis, the study reveals the pressing need for heightened communication efforts and identifies nuanced challenges in bureaucratic structure, particularly varying interests among agencies. The research advocates for intensified communication strategies and underscores the importance of inter-agency coordination, especially concerning established water tariffs.